AFFIRMATIVE ACTION FOR SOUTH AFRICAN CITIZENS: THE ROLE OF THE DEPARTMENT OF LABOUR - Marié McGregor (Obiter, 2022)
In the Auf der Heyde case the Labour Appeal Court held that in the South African context affirmative action should be limited to South African citizens. In this article the author evaluates the case and concludes that this interpretation by the Labour Appeal Court is acceptable in the historical context of the country. The main focus of the article is on the role of the Department of Labour in this regard. The Department provided certain guidelines concerning the issue of citizenship in the context of affirmative action. These guidelines are important but unfortunately not clear. The author recommends that the Department takes a clear policy decision with a view to ensuring that South African citizens are preferred in terms of affirmative action policies.